Analisis Praktik Keperawatan Dengan Intervensi Inovasi Perubahan Posisi Tidur Terhadap Penurunan Kadar Bilirubin Total Pada Bayi Hiperbilirubinemia Yang Diberikan Fototerapi Di Ruang Perinatologi RSUD AM. Parikesit Tenggarong - Hasanah, Rahmatin; Zulaikha, Fatma; Asthiningsih, Ni Wayan Wiwin; Sureskiarti, Enok (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Hyperbilirubinemia is a yellow transforming that develops in newborns and can lead to jaundice complications. Phototherapy is one of the therapies that can be utilized to manage hyperbilirubinemia. In this case, the researcher used an individual sleep position therapy to reduce total bilirubin levels in hyperbilirubinemia newborns getting phototherapy. The findings of observations finished within three days showed that total bilirubin levels decreased to 8.85 mg/dL on the third day. Changes in sleeping position may increase phototherapy's effectiveness in reducing total bilirubin levels in newborns with neonatal jaundice or hyperbilirubinemia.